Functional Brain Plasticity Associated with ACL Injury: A Scoping Review of Current Evidence - T. Neto; T. Sayer; D. Theisen; A. Mierau (Neural Plasticity)
Anterior cruciate ligament (ACL) injury is a common problem with consequences ranging from chronic joint instability to early development of osteoarthritis. Recent studies suggest that changes in brain activity (i.e., functional neuroplasticity) may be related to ACL injury. The purpose of this article is to summarize the available evidence of functional brain plasticity after an ACL injury. A scoping review was conducted following the guidelines of the Joanna Briggs Institute and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. The terms “brain,” “activity,” “neuroplasticity,” “ACL,” “injury,” and “reconstruction” were used in an electronic search of articles in PubMed, PEDro, CINAHL, and SPORTDiscus databases. Eligible studies included the following criteria: (a) population with ACL injury, (b) a measure of brain activity, and (c) a comparison to the ACL-injured limb (contralateral leg or healthy controls). The search yielded 184 articles from which 24 were included in this review. The effect size of differences in brain activity ranged from small (0.05, ACL-injured vs. noninjured limbs) to large (4.07, ACL-injured vs. healthy control). Moreover, heterogeneity was observed in the methods used to measure brain activity and in the characteristics of the participants included. In conclusion, the evidence summarized in this scoping review supports the notion of functional neuroplastic changes in people with ACL injury. The techniques used to measure brain activity and the presence of possible confounders, as identified and reported in this review, should be considered in future research to increase the level of evidence for functional neuroplasticity following ACL injury.